COEXISTING HIGH- AND LOW-CALCIUM MELTS IDENTIFIED BY MINERAL AND MELT INCLUSION STUDIES OF A SUBDUCTION-INFLUENCED SYN-COLLISIONAL MAGMA FROM SOUTH SULAWESI, INDONESIA - Elburg M.; Kamenetsky V.S.; Sobolev A.V.; Nikogosian I.; Foden J. (My University, 2006)
Mineral and melt inclusions in olivines from the most Mg-rich magma from the southern West Sulawesi Volcanic Province indicate that two distinct melts contributed to its petrogenesis. The contribution that dominates the whole-rock composition comes from a liquid with high CaO (up to 16 wt %) and low Al2O3 contents (CaO/Al2 O3 up to 1), in equilibrium with spinel, olivine (Fo85-91; CaO 0.35-0.5 wt %; NiO 0.2-0.30 wt %) and clinopyroxene. The other component is richer in SiO2 (>50 wt %) and Al2O3 (19-21 wt %), but contains significantly less CaO (<4 wt %); it is in equilibrium with cr-rich spinel a low tio2 content, olivine with low CaO and high NiO content (Fo90-94; CaO 0.05-0.20 wt %; NiO 0.35-0.;5 wt %), and orthopyroxene. Both the high- and low-CaO melts are potassium-rich (>3 wt % K2O). The high-CaO melt has a normalized trace element pattern that is typical for subduction-related volcanic rocks, with negative Ta-Nb and Ti anomalies, positive K, Pb and Sr anomalies, and a relatively flat heavy rare earth element (HREE) pattern. The low-CaO melt shows Y and HREE depletion (Gdn/ Ybn ≤41), but its trace element pattern resembles that of the whole-rock and high-CaO melt in other respects, suggesting only small distinctions in source areas between the two components. We propose that the depth of melting and the dominance of H2O- or CO2-bearing fluids were the main controls on generating these contrasting magmas in a syn-collisional environment. The composition of the low-CaO magma does not have any obvious rock equivalent, and it is possible that this type of magma does not easily reach the Earth's surface without the assistance of a water-poor carrier magma. © 2006 Oxford University Press.
Keywords: ANKARAMITES; LOW-CA MAGMA; MELT INCLUSIONS; MINERAL CHEMISTRY; OLIVINE; SYN-COLLISIONAL MAGMATISM